THE IMPACT OF MARKET DEVELOPMENT ON PROMOTION OF ORGANIC AGRICULTURAL PRODUCTS - Đokić, Nenad; Kočić-Vugdelija, Vesna; Berber, Nemanja (Economics of Agriculture, 2018)
Although there are two different approaches to organic market development, the first applied in the USA and the second in countries of EU, it can be seen that on both territories that development is dynamic. Nowadays differences are decreasing while at the same time occurs development of organic agriculture in countries in which it didnt exist before. Increased availability of organic products in different distribution channels and from different parts of the world is actually the consequence of organic market development which sets new tasks for promotion, as for marketing mix instrument. On one hand, direct marketing channels and specialized organic stores are attempting to remain competitive. Besides, there is a need to target increased number of occasional organic buyers. At the same time, possibilities of promoting "organic plus" arguments in order to protect domestic production and consumers from organic market globalisation are being examined. Understanding of organic market development impact on organic products promotion could direct creation of promotion in Serbia, both for internal market, and for organic products export as well.